Penerapan Strategi Pembelajaran Aktif untuk Meningkatkan Hasil Belajar IPA di MTsN Langsa - Zaimah Zaimah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2019)
This study aims to improve student learning outcomes in the field of science studies, the activities carried out in the learning process, by maximizing student activity, the teacher is only as a facilitator and motivator. In learning the teacher uses Active Learning Strategies. Students are expected to have high learning activities so that all the difficulties faced by students can be overcome. The research methodology used was Classroom Action Research (CAR) conducted in 2 cycles. The research subject is class VII4. The data in this study were obtained by test scores and observations. From the results of the learning activities that have been carried out and based on the discussion and analysis that has been carried out, it can be concluded that learning using Active Learning Strategies has a positive impact that can improve student learning outcomes and improve student learning achievement which is marked by increased student mastery in cycle I 6 students or 22.22% were completed and in the second cycle obtained the value of students who completed following the minimum completeness criteria (KKM 70) of 25 students or 92.59%. Then it can be concluded that there is an increase in student learning outcomes using Active Learning Strategies for students of class VII - 4 at MTs Langsa.